Laporan Kasus: Pendekatan Diagnosis dan Tatalaksana Anemia Normokromik Normositer dengan Komorbid Gout Arthritis pada Pasien Geriatri - Muhammad Nawawi (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
A Normocytic normochromic anemia is one of the most common types of anemia found in geriatric patients with chronic diseases or acute bleeding. Upper gastrointestinal bleeding (UGIB) may cause continuous blood loss resulting in decreased hemoglobin levels. This case report discusses a 72-year-old woman who presented to the Emergency Department of Cut Meutia Regional General Hospital with complaints of black stools for four days prior to admission accompanied by epigastric pain, nausea, weakness, and pallor. The patient had a history of long-term use of analgesic and anti-gout medications due to chronic joint pain, which was suspected to be a risk factor for UGIB. Physical examination revealed pale conjunctiva and tachycardia, while laboratory findings showed hemoglobin of 7.1 g/dL, hematocrit of 23.3%, MCV of 82 fL, MCH of 29 pg, and uric acid level of 11.56 mg/dL, leading to the diagnosis of normocytic normochromic anemia caused by UGIB accompanied by gout arthritis. The patient received intravenous fluid therapy, proton pump inhibitors, antifibrinolytic agents, gastroprotective therapy, packed red cell transfusion, and other supportive treatments. During hospitalization, clinical improvement was observed, including cessation of gastrointestinal bleeding, reduced epigastric pain, and increased hemoglobin level to 8.6 g/dL. This case highlights the importance of early diagnosis and comprehensive management in geriatric patients with anemia caused by UGIB and comorbid gout arthritis.